O poder no discurso do delegado de polícia: análise de argumentos retóricos construídos em Relatórios Finais de Inquéritos Policiais - Águeda Bueno do Nascimento (2015)
This work presents an analysis of the rhetorical arguments built during the formulation of eight Police Investigation Final Reports. The analysis is based on Aristotles proposal in classic rhetoric studies. Nevertheless, it also takes into consideration contemporary studies on rhetoric argumentation, especially Parelman & Olbrechts-Tytecas New Rhetoric. This research demonstrates that the legal speech elaborated in the final piece of the police investigation, namely the Final Report, is marked by rhetoric appeals of the logos, ethos and pathos orders, which guard the power represented by the Police Officer. Contrary to common sense, the Art of Rhetoric is a recurrent and skillful strategy used by law practitioners to persuade their interlocutors of the expended thesis. Besides, rhetorical arguments assist the "truth" and the power issued by the Police Officer. The Police Inquiry presents evidence of plausible authorship and materiality involved in a crime, not necessarily irrefutable evidence about the fact under investigation. In this perspective, the Final Report of a Police Inquiry, which highlights the evidence concerning a crime, becomes a privileged space for rhetoric argumentation. As established by the analysis of eight of such reports, this is because the emitter builds his arguments in the domain of the doxa, the values, while aiming at strengthening the "post" of Police Officer and, consequently, at legitimizing its power.